(untitled) (Research, Society and Development, 2021)
It presents a mapping of the scientific production of the graduating students of the Higher Technological Course in Commercial Management of a Higher Education Institution (IES) in the State of Paraíba, during the period between 2017 and 2019.1. It presents a bibliographical survey on the themes: academic-scientific production, research sources and use of the citation resource. The methodological procedures used for the construction of this work took place through an exploratory and documentary research, with an approach focused on action research, using the technique of descriptive statistical analysis for data collection. In the analysis of the data, the students’ informational skills were verified in relation to the search for documents to compose the theoretical framework of the research, as well as the diversity of publications used. Quantifies the use of the direct and indirect citation resource, as well as the use of NBR 6023: 2018, for the construction of references. Finally, the research proposes a structured action for the implementation of an extension project offered by the Campus Library, in order to contribute to the development of the informational skills of graduating students, based on the development of the skills to use the research techniques. academic.